2013
DOI: 10.21913/ijei.v9i2.889
|View full text |Cite
|
Sign up to set email alerts
|

Why students plagiarise from the internet: The views and practices in three Norwegian upper secondary classrooms

Abstract: In a two-part mixed methods study, internet-based plagiarism amongst Norwegian upper secondary students was measured and related to performance level and knowledge of source use. Subsequently, interviews were conducted to explore these students' views on internet access and plagiarism during essay writing. The quantitative part of the study showed that 75% of the 67 students in the study plagiarised from the online sources and that plagiarism accounted for 25% of the total amount of text. Students with a highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
0
13
0
5
Order By: Relevance
“…A 2013 study from Norway found that 75% of final semester humanities students could be easily enticed into serious plagiarism by cunning researchers planting ideal sources online and then correlating them with pupil essays on a given day (Skaar and Hammer, 2013). They found that as many as 75% break the law, that they are articulate in explaining their behaviour, and that the worse their mark in other subjects, the more likely pupils are to plagiarise.…”
Section: Resultsmentioning
confidence: 99%
“…A 2013 study from Norway found that 75% of final semester humanities students could be easily enticed into serious plagiarism by cunning researchers planting ideal sources online and then correlating them with pupil essays on a given day (Skaar and Hammer, 2013). They found that as many as 75% break the law, that they are articulate in explaining their behaviour, and that the worse their mark in other subjects, the more likely pupils are to plagiarise.…”
Section: Resultsmentioning
confidence: 99%
“…Howard & Davies, 2009). Andra menar att initialt bristande språkkunskaper kan skapa situationer där studenterna plagierar (möjligen omedvetet) eftersom de saknar en djupare kunskap om det språk som studierna bedrivs på (Skaar & Hammer, 2013;Song-Turner, 2008). Att plagiat alls uppstår kan alltså handla om ett bedrägligt beteende (som diskuterats ovan), men också om att studenterna inte fått tillräcklig tid för att utveckla sina färdigheter och förmågor gällande just de här situationerna.…”
Section: Akademisk Ohederlighet I Form Av Plagieringunclassified
“…Expansionen av den högre utbildningen genom t.ex. internationalisering skapar också utmaningar i form av att studenter med sämre språkfärdigheter börjar studera (Song-Turner, 2008;Skaar & Hammer, 2013).…”
Section: Vikten Av Att Prata Om Plagiatunclassified
See 1 more Smart Citation
“…Ukpebor and Ogbebor (2013) report that 26.6 % of the 1,000 Nigerian secondary school students they surveyed "use the Internet for plagiarizing" (p. 264). In mixed-method research with 67 Norwegian upper secondary students, Skaar and Hammer (2013) discover that 75 % plagiarized when writing essays while working online. On the basis of his meta-analysis of other research studies, Bennett concludes, "a substantial rise in university student plagiarism has in fact taken place" (2010, p. 139).…”
Section: Scholarly Perspectives On the Relationship Between The Intermentioning
confidence: 99%